Implementation of a Bundle for Gram-Negative Bloodstream Infection: Impact on 30-Day Mortality Analyzed with a Path Model (Epidemiology, Biostatistics, and Public Health, 2025)
INTRODUCTIONGram-negative bacteria are the first cause of community bacteremia and the second cause of nosocomial bacteremia with increasing incidence, relevant morbidity and mortality. The current lack of international guidelines and/or evidence-based care bundles focused on Gram-negative bloodstream infection (GN-BSI) led to challenging management.OBJECTIVESOur aim was to verify whether implementing a bundle in the management of GN-BSI which comprised follow-up blood culture (FUBC), diagnosis imaging (DI) and source control (SC), optimized antibiotic administration (OAA) and shortened treatment duration for uncomplicated BSIs reduced mortality after a GN-BSI event.METHODSThe study population included patients with monomicrobial GN-BSI aged ³18 years enrolled at IRCCS Azienda Ospedaliero-Universitaria di Bologna. From January 2017 to December 2019 patients were administered standard clinical practice (pre-phase); from January 2022 to December 2023 (post-phase) all patients with monomicrobial GN-BSI were managed according to the predefined bundle designed to provide a structured, standardized approach to GN-BSI management, aimed to reduce mortality and improve patient outcomes. To verify the objective of the study a path model was developed, in which the indicator of the study phase was the exposure of interest, 30-day all-cause mortality was the dependent variable and the indicators of FUBC, DI, OAA and SC were set as mediators. FUBC, DI and OAA were posited as first-level mediators and SC as a subsequent mediator, because the decision to undertake FUBC, DI and OAA stems from the patients’ diagnosis, while SC can be undertaken according to FUBC and DI results. Treatment duration was not included in the model because it could be either cause or effect of mortality. The phase indicator was hypothesized as influencing all mediators and the outcome. Several clinical characteristics along with age and gender were included as exogenous variables. From an initial theoretical model, a final model was obtained by discarding non-significant paths and adding paths suggested by modification indices and deemed clinically relevant. Finally, a comparison with other modelling techniques was carried out to verify whether the path model actually added critical information and fitted best to the data.RESULTSOverall 3,355 patients were included, 2,092 were managed in the pre-phase and 1,263 with the bundle. Median age was similar (70.4 ± 16.4 vs. 71.2 ± 16.2 years), as the proportion of male patients (55.4% vs. 58.3%). No significant differences were observed in SOFA score, immunosuppression, septic shock incidence, rates of uncomplicated BSI, while the Charlson Comorbidity Index (CCI) was slightly lower in the post-phase (5.57 ± 2.74 vs. 5.79 ± 3.04; p = 0.011). In post-phase patients the BSI acquisition site showed fewer nosocomial or healthcare-associated cases (64.9% vs. 68.3%, p=0.045) and more community-acquired infections. Escherichia coli was the most common pathogen and was less frequent among post-phase patients (47.8% vs. 53.3%; p = 0.002). Among these patients, higher proportions of appropriate empirical therapy (77.0% vs. 69.2%; p